Peran Arctic Council dalam Menangani Dampak Peningkatan Penggunaan Kapal Pemecah Es di Kawasan Arktik - Putri, Noviar Indira Mikayla; Putranti, Ika Riswanti (Journal of International Relations, 2020)
As a region which holds an important role in keeping the Earth’s temperature, Arctic’s accelerated climate change will not just endanger countries near the Arctic region, but also the world. One of the factors which accelerated the climate change is the increasing use of icebreakers in the past few decades. This research aims to find out the reasons behind the increasing number of icebreakers usage by Arctic Council’s member-states in the past few decades, even though the use of icebreakers harm Arctic Ocean’s sea ice and prevent Arctic Council from fulfilling their purpose. This research uses the theory of liberal institutionalism by Robert Keohane with data collected from conducting literature review. The results of this research show that Arctic Council’s member-states hinder the purpose of the Arctic Council to protect the environment because of their national interests, particularly in economy, that cannot be achieved in the Arctic Council resulting in order to fulfill the interests, countries take their own action.